FASHION CENTER DENGAN PENDEKATAN ARSITEKTUR METAFORA DI BANJARBARU - Siti Amalia; JC Heldiansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The development of the fashion industry in Banjarbaru City shows great potential as a center of creativity and the local economy. Therefore, the Fashion Center in Banjarbaru City is designed as a platform for the production, education, promotion, and appreciation of local fashion works. The resulting design presents a Fashion Center that functions not only as a space for production and exhibition, but also as a communicative and inspiring city icon. The fabric metaphor concept is applied through a semiotic approach by adopting the inherent characteristics of fabric as the basis for creating the building and shaping flexible spaces that represent creativity, identity, and process within the fashion industry..